Synergistic flame retardant effect of cerium‐based DOPO derivative and intumescent flame retardants in polypropylene. Issue 18 (4th March 2023) - Zhang, Yan; Lin, Fenglong; Wu, Yincai; Wang, Shenglong; Liu, Ziteng; Song, Lijun
Abstract: In this study, cerium based DOPO derivative (Ce@DDP) was synthesized by hydrothermal method, and its effects on flame retardancy, thermal stability, and mechanical properties of intumescent flame retardant polypropylene (PP) are investigated. When addition of 17 wt% of intumescent flame retardants (IFR) and 1 wt% of Ce@DDP, the results indicate that the peak heat release rate (PHRR) and peak smoke production rate (PSPR) of the resulted PP composite is reduced by 62.0% and 42.3%, respectively. Meanwhile, the vertical burning rating reaches UL94 V‐0, and the limiting oxygen index (LOI) is 33.8%. Furtherly, the Ce@DDP significantly improves the thermal stability and char formation ability of PP/IFR. Notably, Ce@DDP exhibits better synergistic flame retardant and mechanical strength for PP/IFR than CeO2 . Finally, it was speculated that there was dilution effect and radical quenching effect in gas phase, and catalytic carbonization effect in condensed phase of IFR/Ce@DDP system, and the combined action of the these aspects led to high‐efficiency flame retardant. Abstract : Synergisic flame retardent mechanism.